Utilization of Information Technology and Organizational Commitment to the Reliability of Financial Statements with Internal Control Moderation - Meliana Meliana; Resmiyati Ansar (Bongaya Journal for Research in Accounting (BJRA), 2021)
This study aims to provide empirical evidence of the influence of Information Technology Utilization on the Reliability of Local Government Financial Reports; the effect of Organizational Commitment on the Reliability of Regional Financial Reports; the moderating effect of Internal Control on the Relationship between Organizational Commitment and the Reliability of Local Government Financial Reports; the moderating effect of Internal Control on the relationship between the Utilization of Information Technology and the Reliability of Local Government Financial Reports. The sample of this research is financial administration officials at SKPD in North Maluku Province and consists of 39 respondents. Hypothesis testing using Partial Least Square (PLS) Program. The study results found that information technology did not affect the reliability of local government financial statements. Meanwhile, Organizational Commitment affects the Reliability of Local Government Financial Reports. Internal Control cannot moderate the effect of the Utilization of Information Technology on the Reliability of Local Government Financial Reports. Internal Control is also unable to moderate the effect of Organizational Commitment on the Reliability of Local Government Financial Reports.